Concentration dependence of translational diffusion coefficients for globular proteins - Scott, David J.; Harding, Stephen E.; Winzor, Donald J. (Royal Society of Chemistry, 2014)
This investigation examines published results of traditional diffusion experiments on ovalbumin and bovine serum albumin to determine the extent to which assumed concentration independence of the translational diffusion coefficient is a reasonable approximation in the analysis of boundary spreading in sedimentation velocity experiments on proteins. Although significant positive concentration dependence of the diffusion coefficient (D) for both proteins is predicted by current theories, none has been detected in these experimental diffusion studies performed under the constraints of constant temperature and solvent chemical potential (those also pertinent to sedimentation velocity). Instead, the results are better described by the relatively minor concentration dependence predicted by considering solution viscosity to be an additional source of D–c dependence. Inasmuch as the predicted variation in D for solutions with concentrations below 10 mg mL-1 is within the uncertainty of experimental estimates, these findings support use of the approximate solution of the Lamm equation developed by Fujita for the quantitative analysis of boundary spreading in sedimentation velocity experiments on proteins.